Analysis of eye coordination, arm power and Vo2max in archery athletes in terms of gender - Falaahudin, A.; Saleh, R. A. P.; Triprayogo, R.; Nadzalan, A. M. (International Journal of Multidisciplinary Research and Analysis, 2024)
Archery is a sport that prioritizes endurance, strength, accuracy, coordination, flexibility and balance to form archery techniques. These factors must all be supported by training, excellent and long-lasting physical condition. Therefore, every archery athlete must have excellent physical condition when facing a competition or championship. In performance sports, a person or athlete needs good physical condition in addition to technical ability. The physical training provided must be in accordance with the characteristics of the number being developed and in accordance with the physical condition of the swimming athlete himself. Strength is an important basic element in supporting movement skills. Strength is required in all sports for all activities that depend on strength. The strength that works more in archery is muscle strength. Muscle strength refers to a muscle group that is capable of carrying out long contractions. Arm muscle strength is the ability of a muscle or group of muscles to contract dynamically or statically by pulling a weight for a relatively long time, to provide encouragement to create consistency of movement from the beginning to the end of archery. Therefore, the strength of the arm muscles and the physical condition of the archer are very important to achieve optimal results. Through this research, researchers are interested in conducting research with the title analysis of hand eye coordination, arm power and VO2max of archery athletes in terms of gender. After the results of the physical condition analysis are obtained, the researchers hope that archery coaches and athletes can further optimize competition preparation and achieve the best performance. The method in this research program is quantitative descriptive. With physical condition test instruments for archery athletes. This study aims to determine the results of the analysis of hand eye coordination, arm power and VO2max of archery athletes in terms of gender. The population in this study was the KONI archery athletes from Bantul Regency, totaling 24 athletes. Based on the research results, it can be concluded that arm length, eye-hand coordination and VO2max of KONI archery athletes in Bantul Regency are in the medium category.